Advanced Hand Gesture Controlled Television Using Data - KUMAR,, M. ASHOK; KUMAR, MR.D. (IJRDO -Journal of Computer Science Engineering, 2015)
Human interaction with wearable computers is a challenging research issue,especially when combined with augmented reality applications. Natural interaction withvarious devices should be simple and at the same time intuitive for any user. This projectrepresents the design and implementation of a novel interactive hardware which recognizescertain hand gestures and responds in a way of controlling a remote television. The hardwareis made as a data glove with an accelerometer and stretch sensor attached to it. Controlparameters are calculated by an accelerometer and stretch sensor mounted on the glove,which detects positions of a user’s palm in a 3D space. Slow palm rotation is translated intocommands for the volume control, ON/OFF, and channel switching. RF transmitterconnected to the accelerometer sends the current palm and hand coordinates to the remoteunit. The TV control is managed by an RF receiver and microcontroller which translates thereceived data to TV commands.